6957 5-Year Follow-Up of Acute, micro, and Macrovascular Complications of Patients With Type 2 Diabetes Managed by a Multi-Disciplinary Team In A Hospital in Northeastern Mexico - Romero Ibarguengoitia, Maria Elena; Morales Rodríguez, Devany Paola; Garza-Silva, Arnulfo; Rivera-Cavazos, Andrea; Francisco Fernández-Chau, Iván; Cepeda-Medina, Andrea Belinda; González-Cantú, Arnulfo (Journal of the Endocrine Society, 2024)
Abstract Disclosure: M. Romero Ibarguengoitia: None. D.P. Morales Rodríguez: None. A. Garza-Silva: None. A. Rivera-Cavazos: None. I. Fernández-Chau: None. A. Cepeda-Medina: None. A. González-Cantú: None. Type 2 Diabetes Mellitus (T2DM) is a condition associated with various acute and chronic complications, which constitute the leading cause of disability, morbidity and mortality globally. During the SARS-CoV-2 pandemic, vulnerable individuals such as those with T2DM faced a restriction in access to primary healthcare services. Therefore, we decided to compare the presence of micro and macrovascular complications before and during the SARS-CoV-2 pandemic, as well as the incidence of acute complications. A retrospective observational cohort study from 2018 to 2022 was conducted in a hospital in northeastern Mexico on patients with T2DM who were treated by a multidisciplinary team composed of an internist or geriatrician based on the patient's age, endocrinologist, nutritionist, and other diabetes-related specialties. Levels of HbA1C, fasting serum glucose (FSG), low-density lipoprotein cholesterol (LDLc), blood pressure (BP), and microalbuminuria were analyzed. Consequently, presence of micro and macrovascular complications and incidence of acute complications was described. A total of 999 subjects were analyzed, 516 (51.7%) males, with an average age (SD) of 60.1 (12.7) years. There was an increase in the proportion of patients with adequate glycemic control based on HbA1C of 15.2% between 2018 and 2022 (p<0.001) and a 42.3% increase in FSG control during the same period (p<0.001). LDLc showed a decrease in the control proportion of 5.1% between 2018 and 2022 (p<0.001). Systolic BP control in 2018 was 82.7% and 80.1% in 2022 (p<0.001). Diastolic BP control in 2018 was 89.6%, with an increase to 91.4% in 2022 (p=0.01). Microalbuminuria control increased from 80.5% in 2018 to 89% in 2022 (p=0.002). There were 78 (7.8%) cases of microvascular complications, with diabetic neuropathy being the most prevalent (n=35, 3.6%), and a higher incidence in 2021 with 15 (1.6%) cases. A total of 15 (1.5%) patients presented a macrovascular complication, with ischemic heart disease being the most frequent with 11 (1.1%) subjects, and a higher incidence of cases in 2021 (n=4, 0.4%). Hypoglycemia was found to be the most frequent acute complication with 14 (1.4%) cases, with a higher incidence in 2020 (n=5, 0.5%). The low incidence of complications in our population, emphasizes the importance of coordinating patient’s care between a multidisciplinary team to maintain an overall disease control, optimize T2DM treatment and enhance patient’s quality of life. Presentation: 6/1/2024